â€œMENCARI KESEJAHTERAAN MELALUI RITUAL RUWATAN MASALâ€ - Widagdo, M. Bayu (Faculty of Social and Political Sciences Diponegoro University)
Abstract: Ruwatan is a kind of traditional art form, appear and developing notably in Java ethnic. This ritual aim to breaking out an unfortunate called â€œsukertaâ€ that often meaning â€œunfortunate innatelyâ€ that is natural cause, so that make unbalance in their live. This ritual in essence is a form of how ancient tribesman are striving to get a prosperous live. Afterwards, this ritual now have been developed in any new tradition ceremony like the autentic one but in reality have already leaved from the autentic ritual of ruwatan. When the medium is already changed to be purpose, ruwatan now have became a comodity in cultural industries, where prosperous is being main purpose no more.Keywords: comodification, prosperous, ethnic culture,Â permalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3206